Use of yeasts for the biological control of toxigenic Aspergillus sp. associated with Zea mays L. - Sánchez Purihuamán, Marilín (2026)
Zea mays "maize" is one of the most important staple foods for both humans and animals, but it is highly susceptible to pathogens such as toxigenic Aspergillus flavus. Yeasts, however, have the potential to control the growth and activity of toxigenic fungi, representing a viable and economical alternative for biocontrol. This study is aimed at evaluating the efficiency of yeasts in controlling toxigenic A. flavus associated with maize grains. To achieve this, toxigenic A. flavus and yeast isolates were obtained and identified, then coinoculated in vitro to assess their effect on mycelial growth inhibition and total aflatoxin production through yeast-derived volatile organic compounds (VOCs). We found that 147 of the isolated yeasts, when coinoculated with A. flavus, reduced mycelial growth up to 89%. VOCs from five yeast strains of the genera Saccharomyces and Meyerozyma inhibited colony growth up to 86% and induced changes at both the macro- and micromorphological levels in toxigenic A. flavus. Additionally, VOCs from four yeast strains reduced total aflatoxin levels up to 98%. In conclusion, one yeast strain, identified as Meyerozyma caribbica, effectively inhibited both mycelial growth and toxin production in toxigenic Aspergillus sp., demonstrating its potential as a biocontrol agent to reduce fungal contamination in maize grains.